Usulan Perancangan Tata Letak Gudang III dengan Metode Systematic Layout Planning pada PT XYZ - Theresia, Santa; Andrianti, Irma; Sugeng, Bambang (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The layout design at Warehouse III of XYZ Company is expected to solve the problem of material flow patterns and material movement distances which are currently still ineffective. Designing the right layout is carried out to increase warehouse productivity and help the company regulate the flow of processes and material movements so that it runs easier and smoother. This study aims to provide an efficient and effective layout of the proposed warehouse layout, by paying attention to the flow pattern and the optimal area area in increasing the productivity of warehouse III. Therefore, the Systematic Layout Planning (SLP) method is used in designing the layout of Warehouse III. The results of the study showed that there was a significant difference in the total material displacement distance from the initial layout. In the proposed layout, there is a reduction in the material displacement distance from 75.2 to 60.4 .